2021
DOI: 10.1002/ddr.21834
|View full text |Cite
|
Sign up to set email alerts
|

CircMYBL2 regulates the resistance of cervical cancer cells to paclitaxel via miR‐665‐dependent regulation of EGFR

Abstract: Circular RNAs are considered to be associated with cancer resistance. This study aims to investigate the function and mechanism of circMYBL2 in paclitaxel (PTX) resistance of cervical cancer (CC). The expression of circMYBL2, miR-665 and epidermal growth factor receptor (EGFR) was investigated using quantitative real-time polymerase chain reaction assay. Cell viability, cell colony number, cell proliferation, apoptosis and lactate dehydrogenase (LDH) were detected by 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Consequently, this impedes mitosis and fosters the demise of tumor cells, yielding potent antitumor effects [16][17][18]. Relevant clinical studies have corroborated these findings, indicating that the preoperative utilization of paclitaxel in the treatment of cervical cancer patients can substantially reduce tumor size, facilitating the complete removal of tumor lesions during subsequent surgical procedures, subsequently diminishing the risk of recurrence and metastasis post-surgery [19,20]. Paclitaxel, cisplatin and carboplatin have all demonstrated individual effectiveness in the treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, this impedes mitosis and fosters the demise of tumor cells, yielding potent antitumor effects [16][17][18]. Relevant clinical studies have corroborated these findings, indicating that the preoperative utilization of paclitaxel in the treatment of cervical cancer patients can substantially reduce tumor size, facilitating the complete removal of tumor lesions during subsequent surgical procedures, subsequently diminishing the risk of recurrence and metastasis post-surgery [19,20]. Paclitaxel, cisplatin and carboplatin have all demonstrated individual effectiveness in the treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, recent studies have found that miR-665 is signi cantly downregulated in TNBC, and the upregulation of miR-665 is positively correlated with the survival time of patients with TNBC [16]. In addition, miR-665 is inextricably associated with paclitaxel resistance in cervical cancer cells [31]. However, the mechanism of miR-665 resistance to paclitaxel in TNBC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, circMTO1 enhanced chemoresistance via sponging miR-6893 in cervical cancer ( Chen et al, 2019 ). CircMYBL2 governed paclitaxel resistance via targeting miR-665/EGFR axis in cervical cancer ( Dong et al, 2021 ). Hsa_circ_0074269 increased cisplatin resistance via mediating miR-485-5p and TUFT1 in cervical cancer ( Chen et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%